(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
In Indonesia, the long-standing presence of a dedicated building for storing rice (granary) in traditional houses serves as clear evidence of the significance of agricultural produce within the country’s cultural heritage. Before the advent of modern financial systems, rice functioned as a symbol of wealth and prosperity for indigenous communities, and for this reason, it was kept in a specialized structure known as a granary. In relation to traditional Bawean houses, this structure is referred to as a Dhurung, a standalone form that is typically situated at the front of the house. With the gradual shift towards modernization, however, more practical storage solutions, such as using boxes placed in the kitchen or cooking areas, have emerged, causing the traditional function of the rice barn to undergo a significant transformation. The Dhurung, which once served as a vital storage facility for rice, has accordingly evolved in response to changing lifestyles and needs. This study therefore aims to investigate the transformation of the Dhurung from a rice storage facility into a multipurpose space that is often used for gathering and socializing on the front porch of Bawean Island’s traditional houses. The primary objective of this research is to identify the underlying motivations that have driven the functional shift of the Dhurung, while also examining the dynamics of cultural adaptation and the evolving needs of communities. By examining the transformation of the Dhurung using Qualitative Method, this study seeks to contribute to a deeper understanding of the cultural significance of granary in Indonesia and to inform future studies on the diversity of rice barns across Indonesia. Through exploring the transformation of traditional structures like the Dhurung, this research promotes a more nuanced understanding of the complex relationships between cultural heritage, community needs, and sustainable development.